Plickers Media to Boost 10th Graders’ Motivation and Performance through Number Head Together Cooperation - Septiza; Ahmad Yani T; Nurfadilah Siregar; Edy Yusmin; Hamdani (Indonesian Journal of Educational Research and Review, 2025)
During mathematics lessons, most teachers still used limited teaching media, such as blackboards, that tended to be monotonous. This had an impact on low motivation and learning outcomes for students. This study analyzed the effect of implementing Plickers media in the NHT type cooperative learning model on student motivation and learning outcomes in class X. The type of this research was quasi experimental with a nonequivalent posttest only control group design, using a quantitative approach. All tenth-grade students were the population. The sample used purposive sampling, with class XC consisting of 33 students as the experimental class. Data collection instruments included non-test methods such as a learning motivation questionnaire with 18 statements and a learning outcome test consisting of 5 multiple-choice questions with varying difficulty levels. The questionnaire data were converted using the Method of Successive Interval, and the students' learning outcomes were analyzed using the t-statistical test after meeting the prerequisites of homogeneity and normality. The research showed that student motivation and learning outcomes in classes that implemented Plickers media in the NHT cooperative learning model were better than in classes without Plickers media. Thus, it was concluded that applying Plickers media in the NHT type cooperative learning model significantly impacted students' motivation and learning outcomes. This research implied that applying Plickers media in the NHT type cooperative learning model could be an alternative for teachers to enhance student motivation and learning outcomes.